Status of mushroom production: Global and national scenario - Bijla, Shweta; Sharma, Ved Parkash (Mushroom Research, 2023)
Mushroom cultivation has the potential to be a very lucrative agribusiness venture which addresses several present-day concerns such as resource utilization, circular economy, job creation, sustainability, unpredictable weather, and nutritional security in the nation. In India, since majority of the farmers are small-scale and marginal landowners with limited capital, mushroom production is a boon as it uses agricultural waste for growing medium and requires less land, water, and finance. Growing the production of mushrooms would increase their availability throughout the country, which will further help to reduce nutritional insecurity and also raise the income of small and marginal growers. Mushrooms have immense potential for medical and nutraceutical purposes. However, our nation has recently begun to produce and consume mushrooms. Many obstacles faced by mushroom growers including a lack of technical knowledge, inadequate infrastructure, an unorganized market, expensive inputs, etc., still need to be addressed with sufficient research and additional legislative solutions tailored to the requirements of Indian mushroom growers. The paper will describe the growth of mushroom economy globally and in India as well. Some challenges and opportunities are also discussed at the end.